Compound Words in Lover Album by Taylor Swift: A Morphological Study - Nurwulan, Galih Rinanda; Heryono, Heri (JALL (Journal of Applied Linguistics and Literacy), 2025)
This study aims to analyze the morphological processes of compound words found in the lyrics of Lover, an album by Taylor Swift. The research employs a qualitative descriptive method, focusing on identifying the types, functions, and meanings of compound words present in the album's lyrics. The results reveal six types of compound words, categorized as adverbial compounds, verbal compounds, and nominal compounds, with nominal compounds being the most prevalent. Words such as sweetheart and daylight represent themes of affection and hope, while terms like heartbreak and homecoming convey emotional nuances associated with love, loss, and relationships. This research highlights the role of morphology in songwriting and demonstrates how compound words enhance the emotional and thematic depth of the lyrics. The findings offer new insights into the intersection of language and art, emphasizing the creative use of morphological processes in popular music.